1990
DOI: 10.1111/j.1365-2842.1990.tb01417.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental cutting behaviour of mica‐based and apatite‐based machinable glass‐ceramics

Abstract: Some recently developed industrial ceramics have excellent machinability properties. The objective of this study was to evaluate the dental cutting behaviour of two machinable glass-ceramics, mica-containing Macor-M and apatite- and diopside-containing Bioram-M, and to compare them with the cutting behaviour of a composite resin typodont tooth enamel and bovine enamel. Weight-load cutting tests were conducted, using a diamond point driven by an air-turbine handpiece, While the transverse load applied on the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…11,23,25 Therefore, cleavage of mica crystals localizes the fracture of the glass matrix in the microscopic scales and facilitates the formation of powered chips. 19,20 In this study, the outcome that the machinability of Vita MK II was lower than that of the new machinable glassceramic containing calcium-mica (Group 2) may be the result of Vita MK II without cleavage plane.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…11,23,25 Therefore, cleavage of mica crystals localizes the fracture of the glass matrix in the microscopic scales and facilitates the formation of powered chips. 19,20 In this study, the outcome that the machinability of Vita MK II was lower than that of the new machinable glassceramic containing calcium-mica (Group 2) may be the result of Vita MK II without cleavage plane.…”
Section: Discussionmentioning
confidence: 73%
“…19,20 In a more recent study, Watanabe et al 21 and Kikuchi et al 22 evaluated machinability of dental materials through volume loss of materials which was calculated from the density and the weight loss. This method applies to uniformly dense materials.…”
Section: Discussionmentioning
confidence: 99%
“…However, these previous studies did not perform quantitative evaluations for machinability. Meanwhile, Taira et al conducted quantitative assessments of machinability of bovine enamel and tooth-model materials [10][11][12] . The study examined the machinability of the mica-containing glass-ceramic, apatite-and diopside-containing glass-ceramic, and resin composite 11) , and showed that hardness as well as machinability of these materials differed from that of bovine enamel.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the difference in the characteristics between natural teeth and resinbased materials, it is difficult for dental students to experience the grinding sensation of natural teeth during the tooth preparation training which is based on the use of phantom model teeth. To overcome this issue, some materials have been investigated for the model teeth [8][9][10][11][12] . Previous studies examined the mechanical properties of restorative materials, such as porcelain, filler-dispersed resin composites, and polymer-infiltrated ceramic network (PICN) composites 8,9) as potential materials for teeth used in the training model.…”
Section: Introductionmentioning
confidence: 99%
“…Rotational frequency of dental handpieces has been measured using methods such as mechanical tachometers, 12,13 stroboscopes, 1416 optical counting devices, 1720 magnetic systems, 2124 and sound frequency detectors. 25 Of these methods, sound frequency has been one of the easiest techniques to implement.…”
Section: Discussionmentioning
confidence: 99%